THE REALITY OF E-GOVERNMENT IN THE IMPLEMENTATION OF THE STATE CIVIL APPARATUS INFORMATION SYSTEM IN BANGLI REGENCY - Widhiasthini, Ni Wayan; Nida, I Dewa Refortana; Utami, Made Srinitha Millinia (CosmoGov: Jurnal Ilmu Pemerintahan, 2024)
This study explores the use of the State Civil Apparatus Information System, known as Sistem Informasi Aparatur Sipil Negara (SIASN) in Bangli Regency and examines various factors that affect its implementation. Researchers use qualitative descriptive research methods with an empirical approach. Data collection is done through interviews, observations, and document studies. The findings show that the implementation of e-Government and SIASN in Bangli Regency is very successful, especially in the field of personnel services such as Needs Planning, Data Rejuvenation, Promotion, Employment Status, Agency Mutation, and Dismissal of Civil Servants. SIASN also offers excellent accessibility, transparency, effectiveness, and service efficiency. However, there is a need to increase the availability of computers to improve SIASN implementation. The success of e-government in Bangli Regency is supported by effective communication, adequate human resources and technology, commitment from implementers, and a well-organized bureaucratic system. On the other hand, inhibiting factors include limited computer availability, budget constraints, system repairs, and meeting needs. Overall, the implementation of e-Government and SIASN has had a positive impact on the quality of services provided to the State Civil Apparatus in Bangli Regency, thereby increasing accessibility, transparency, effectiveness, and efficiency of servicesgb777